Readiness of Exercise Physiologists, Physiotherapists and Other Allied Health Professionals to Respond to Gender-Based Violence: A Mixed-Methods Study - Wheatley, Lauren (Violence against women, 2025)
Experiencing gender-based violence (GBV) is associated with health conditions that are common indications for referral to exercise physiologists, physiotherapists and other allied health professionals (AHPs). The readiness of AHPs to identify and respond to GBV is currently unknown. This study aimed to determine the readiness of AHPs to respond to a person who had experienced GBV. Participants completed the modified Physician Readiness to Manage Intimate Partner Violence Survey (PREMIS) and/or an interview. The AHPs felt underprepared, had low perceived knowledge and lacked confidence to respond to and support people who have experienced GBV, despite recognition of the importance and agreement of the relevance to AHPs’ practice.